Effect of Argon Gas on the Structure and Optical Properties of Nano Titanium Oxide Prepared by PLD - Hattab, Farah (Iraqi Journal of Science, 2024)
In this research the effect of laser energy by using argon gas on the some physical properties of semiconductor film of TiO2, was studied used Q-Switch Nd:YAG laser in different energies (600-1000) mJ with temperature 100 0C for glass substrate under vacuum nearly 10-3 - - , and by AFM test the roughness of films increased when the energy of laser increased too. The values of roughness between (6.77-13) nm, therefore the thicknesses increased to change from (34.88 - 165.48) nm, so the absorption of film increased because of the thickness of the film increased and we can get the optical energy gap between (3.6-3.9) eV.